KESALAHAN MAHASISWA DALAM MEMECAHKAN MASALAH PADA TOPIK UKURAN PENYEBARAN DATA - Rosidah; Fadhil Zil Ikram (MaPan : Jurnal Matematika dan Pembelajaran, 2022)
The measure of spread is one of the concepts in Statistics that students find complicated. We have to use a specific formula or concept for a specific situation or contextual problem. As a result, people or students sometimes made mistakes or errors in solving statistics problems. Therefore, research to investigate errors made in solving problems involving a measure of spread is necessary. This study aims to describe students' errors in solving problems related to the measure of dispersion. Researchers used a qualitative descriptive approach. We administered the test during the even semester from January to June in the year 2021. The participants were 80 undergraduate students who have completed or taken statistics courses. This test consists of 2 questions that are related to each other. Researchers used the three main steps to analyze the data which consist of data condensation, data display, and verifying and drawing the conclusion. We obtained the data related to students' errors from their test results. The results showed that more than 50% of students still make mistakes on every problem. The mistakes made by participants consisted of the use of formulas, miscalculations, the use of known data, the use of concepts, not giving conclusions, and inconsistencies.